2023
DOI: 10.3390/plants12244086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post-Anthesis Irrigation on the Activity of Starch Synthesis-Related Enzymes and Wheat Grain Quality under Different Nitrogen Conditions

Lang Xin,
Yuanyuan Fu,
Shoutian Ma
et al.

Abstract: To develop optimal management strategies for water and nitrogen fertilizer application in winter wheat cultivation, we conducted a potted experiment to investigate the effects of different irrigation levels and nitrogen fertilizer treatments on the activity of starch synthesis-related enzymes and the grain quality of winter wheat. The potted experiment consisted of three irrigation levels, with the lower limits set at 50–55% (I0), 60–65% (I1), and 70–75% (I2) of the field capacity. In addition, four levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…The above enzyme activities are significantly affected by nitrogen application rates. Insufficient or excessive nitrogen application can lead to varying degrees of decreases in key enzymes involved in starch synthesis, with varying impacts on various stages of starch synthesis [15]. This study found that, under different treatments, the activities of key enzymes in grain starch synthesis (ADPG-PPase, SSS, GBSS, SBE) showed a tendency to increase and then decrease with the increase in days after anthesis, which was in agreement with the findings of Li et al [36].…”
Section: Effect Of Nitrogen Application Rate On Starch Metabolism And...supporting
confidence: 91%
See 2 more Smart Citations
“…The above enzyme activities are significantly affected by nitrogen application rates. Insufficient or excessive nitrogen application can lead to varying degrees of decreases in key enzymes involved in starch synthesis, with varying impacts on various stages of starch synthesis [15]. This study found that, under different treatments, the activities of key enzymes in grain starch synthesis (ADPG-PPase, SSS, GBSS, SBE) showed a tendency to increase and then decrease with the increase in days after anthesis, which was in agreement with the findings of Li et al [36].…”
Section: Effect Of Nitrogen Application Rate On Starch Metabolism And...supporting
confidence: 91%
“…Among them, the ADPG-PPase, SSS, GBSS, and SBE under the CK1 (300 kg•ha −1 ) treatment were significantly lower than those under the A1 (255 kg•ha −1 ) treatment, with decreases of 5-23%, 3-20%, 3-20%, and 8-24%, respectively, resulting in a decrease of 7-18% in the starch content. Xin et al [15] believe that wheat can increase ADPG-PPase, SSS, GBSS, and SBE activity and yield at a nitrogen application rate of 240 kg•ha −1 . However, when the nitrogen application rate is 300 kg•ha −1 , both the enzyme activity and yield mentioned above decrease, which may be due to differences in geographical and climatic conditions.…”
Section: Effect Of Nitrogen Application Rate On Starch Metabolism And...mentioning
confidence: 99%
See 1 more Smart Citation